Smart partnership: Plant-rhizobacteria associations - Shamsuddin, Zulkifli (2005)
Malaysia is one of the twelve mega~biodiversity countries blessed with diverse forms of microflora and fauna together with their complex microbial associations. The unique smart partnership between root-associated and colonizing bacteria (rhizobacteria) and plants is vital for the sustainability of the global ecosystem namely the contribution towards nutrient cycling and plant growth. Various symbiotic and associative rhizobacterial associations are discussed in this paper with focus on the contribution of rhizobia and plant growth promoting rhizobacteria (PGPR) in legumes and non-leguminous economic crops under acidic, humid tropical environment. Different plant-rhizobacterial adaptations are exemplified to demonstrate the unique abilities of these associations to overcome the adverse effects of soil environment. Locally isolated Bradyrhizobium (UPMR29, 48), Azorhizobium (UPMR42, 43, 44), and PGPR (Bacillus sphaericus UPMBlO, UPMB12, 13, 14) strains show varying competitiveness and compatibility in their symbiotic and nonsymbiotic associations with several leguminous covers, pasture and food legumes (groundnut, winged bean, vegetable soybean) and non-leguminous food (sweet potato, banana) and economic crops (oil palm). The ability of these bacteria and their plant associations to overcome abiotic stresses, increase plant nutrient uptake, growth and yield are highlighted. The competitive PGPR strains namely Bacillus sphaericus UPMBlO was characterized and the optimum growth requirement, inoculum carrier (ground oil palm frond) and inoculum production technique identified. Anew cost-effective and high quality inoculant production technology for these rhizobacteria with high commercial potential is featured. In Malaysia, there is greater possibility for more smart partnerships involving many plant-rhizobacterial associations to be developed for economic benefits to the nation.